2010
DOI: 10.1007/s12010-010-8946-8
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Biocellulose Nanofibers Production from Agricultural Renewable Resources: Preliminary Study

Abstract: In the present preliminary study, we report results for the biocellulose nanofibres production by Gluconacetobacter xylinus. Production was examined by utilizing different feedstocks of single sugars and sugar mixtures with compositions similar to the acid hydrolyzates of different agriculture residues. Profiles for cell proliferation, sugar consumption, and the subsequent pH changes were thoroughly analyzed. Highest biocellulose production of 5.65 g/L was achieved in fructose medium with total sugar consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 38 publications
4
43
1
1
Order By: Relevance
“…Instead of using single sugars as feedstocks, Dahman et al investigated the ability to produce bacterial cellulose from multiple sugars. Sugar compositions similar to those found in acid hydrolysates of some agricultural residues were utilized with Gluconacetobacter xylinus as the bacteria [10Dah]. Under identical conditions, the bacterial production from single sugars varied from 1.1 to 5.7 g/l compared to 2.4 to 5.2 g/l for the mixed sugars.…”
Section: Agricultural Residues As Feedstocks For Production Of Bactermentioning
confidence: 98%
“…Instead of using single sugars as feedstocks, Dahman et al investigated the ability to produce bacterial cellulose from multiple sugars. Sugar compositions similar to those found in acid hydrolysates of some agricultural residues were utilized with Gluconacetobacter xylinus as the bacteria [10Dah]. Under identical conditions, the bacterial production from single sugars varied from 1.1 to 5.7 g/l compared to 2.4 to 5.2 g/l for the mixed sugars.…”
Section: Agricultural Residues As Feedstocks For Production Of Bactermentioning
confidence: 98%
“…BC, whether nanofibre or nanocrystal is a much desired biotech material with wide applications in the paper and textile industry and highly demanded in biomedical outfits for treatment of high degree burns, artificial artery for drug delivery, scaffold for tissue engineering as well as food additives and other industrial applications (Klemm et al, 2001;Chalwa et al, 2009;Dahman et al, 2010;Lee et al, 2013;Shah et al, 2013;Keshk, 2014;Zhijun et al, 2014;Tsuoko et al, 2015;Sulaeva et al, 2015;Cacicedo et al, …”
Section: Introductionmentioning
confidence: 99%
“…BC can be prepared from fermentation process throughout a specific type of bacterial strains. The unique structure of BC is formed from the pure form of cellulose nanofibers, which contains a high degree of crystallinity associated with a high degree of polymerization [6]. These exceptional properties also possess potential forerunner for development technologies in the various significant area, such as tissue engineering, sustainable polymeric biomaterials, and green nanocomposites [7].…”
Section: Introductionmentioning
confidence: 99%
“…BC nanofiber reinforced into PLA nanocomposite has gained much consideration because of their low density, inexpensive, non-abrasiveness; very low toxicity and degradable properties. Several reports [6][7][8] revealed that the mechanical and thermal properties of degradable polymers are enhanced when using an appropriate Compatibilizer with the cellulose nanofibers. The non-uniform dispersion can cause inferior tensile strength and high-water absorption.…”
Section: Introductionmentioning
confidence: 99%